Crystal structure of {hydridotris[3-(t-butyl)-5-isopropylpyrazol-1-yl-κN3]borato}thallium(I), C30H52BN6Tl - Fujisawa, K.; Shimizu, D.; Tiekink, Edward R. T. * (De Gruyter Open, 2021)
C30H52BN6Tl, monoclinic, P21/n (no. 14), a = 9.611(3) Å, b = 17.586(5) Å, c = 19.710(6) Å, β = 98.374(7)°, V = 3295.8(17) Å3, Z = 4, Rgt(F) = 0.0152, wRref(F2) = 0.0381, T = 182 K.